2004
DOI: 10.1002/ceat.200401989
|View full text |Cite
|
Sign up to set email alerts
|

Gas Flow Behavior in a Two‐Phase Reactor Stirred with Triple Turbines

Abstract: Gas behavior was studied in a gas-liquid reactor stirred with multiple turbines. Triple PBTs pumping either down or up and BT-6's were used. The behavior of coalescing (water) and non-coalescing (sodium sulfate solution) systems was investigated. The gas phase behavior was characterized by means of the RTD and modeled with the axial dispersion model. This model was confirmed to interpret the experimental data well for water and satisfactorily for the coalescence-inhibiting solutions. The influence of the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Though the scope of this study, it is also interesting to mention that the Peclet values (equal to 1/a) determined with the regression technique based on Eq. (29) are obviously in good agreement with those obtained by considering only the ascending part of the experimental RTD curve, e.g., Majírová et al [10].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Though the scope of this study, it is also interesting to mention that the Peclet values (equal to 1/a) determined with the regression technique based on Eq. (29) are obviously in good agreement with those obtained by considering only the ascending part of the experimental RTD curve, e.g., Majírová et al [10].…”
Section: Discussionsupporting
confidence: 72%
“…On the contrary, Svihla et al [9], who modeled the system with three ideally mixed stages with superimposed plug flow, concluded that the gas hold-up in a stirred vessel cannot be determined with satisfactory accuracy from the measurement of gas RTD even when using a tracer of very low solubility. Nocentini et al [4,5], Pinelli and Magelli [6], Majírová et al [10] and Linek et al [11] all adopted the axial dispersion model for modeling the gas phase, which proved quite accurate in predicting its behavior. Only the ascending part of the RTD curve was used by the first authors to determine the model parameter as the tail was affected by tracer solubility, while the whole curve was used by Linek et al [11] who employed a tracer of lower solubility (helium).…”
Section: Introductionmentioning
confidence: 98%
“…Although the presence of small quantities of SDS is expected to somewhat decrease the maximum stable bubble size (due to the reduction of static surface tension), this tendency is counteracted by the tendency to impede bubble breakage due to the development of the Marangoni elastic forces . On the other hand, bubble coalescence rate is strongly hindered by the presence of very small SDS concentrations. , Consequently, the fine bubbles generated at the screen/grid mixing elements will be maintained for longer distances downstream, thereby yielding high specific interfacial areas which should enhance the value of the volumetric mass-transfer coefficient. This was experimentally confirmed by Chen and by the population balance simulation results undertaken by Azizi and Al Taweel .…”
Section: Resultsmentioning
confidence: 99%
“…18 On the other hand, bubble coalescence rate is strongly hindered by the presence of very small SDS concentrations. 49,82 Consequently, the fine bubbles generated at the screen/grid mixing elements will be maintained for longer distances downstream, thereby yielding high specific interfacial areas which should enhance the value of the volumetric mass-transfer coefficient. This was experimentally confirmed by Chen 10 and by the population balance simulation results undertaken by Azizi and Al Taweel.…”
Section: Effect Of Interfacial Characteristicsmentioning
confidence: 99%
“…For sparged stirred tanks of standard geometry mainly the date of the spatial distribution of gas holdup 5 and bubble size distribution (BSD) 6 in equipment stirred has been investigated with a single impeller 7 or a dual 8,9 or triple turbine 10,11 . The principal advantage of GIMAC and SAR over SLR and JLR lies in the avoidance of compression and recovery equipment.…”
Section: Introductionmentioning
confidence: 99%